Hubungan Tingkat Pengetahuan Terhadap Sikap Masyarakat Pada Orang Dengan Gangguan Jiwa - Asriani; Fathra Annis Nauli; Darwin Karim (STIKes Payung Negeri Pekanbaru, 2020)
A person with mental disorder is someone who experiences disturbances in thoughts, behaviors and feelings that are manifested in the form of a group of symptoms and cause obstacles in carrying out their functions. People with mental disorders are still discriminated against, ridiculed, shunned, ignored, ostracized and considered a disgrace in the community. This treatment is due to the lack of public knowledge of people with mental disorders. This study aims to determine the relationship of the level of knowledge on people's attitudes in people with mental disorders with a descriptive correlation research design. The research sample was 99 respondents taken based on inclusion criteria using cluster sampling techniques. The measuring instrument used was a questionnaire sheet that had been tested for validity and reliability. The analysis used is univariate analysis to determine the frequency distribution and bivariate using chi square test. The results showed that of the 99 respondents who had a good level of knowledge as many as 64 respondents (64.4%), respondents who had a positive attitude were 55 respondents (55.5%). The statistical test results obtained p value = 0,000 ˂ α (0.05), then Ho is rejected, so it can be concluded that there is a significant relationship between the level of knowledge of people's attitudes towards people with mental disorders. It is recommended for the community to be able to increase knowledge so as to have a positive attitude to people with mental disorders.